ANALISIS HUBUNGAN TINGKAT KEJAHATAN DAN PERTUMBUHAN EKONOMI DI INDONESIA - Derry Angling Kesuma (AKSELERASI: Jurnal Ilmiah Nasional, 2019)
The prevalence of crime in an area will hinder business and have an effect on increasing poverty and income of an area. The type of research method used is a qualitative method. The data used in this research is secondary data. This study uses panel data from 31 provinces in Indonesia between 2013-2018. Secondary data collection was obtained from BPS, namely the Human Development Index (IPM), total investment, general crime index (CR 1), Economic crime or corruption index (CR 2) to GRDP to measure economic growth. The parameters that will be sought in the study are to measure the general crime index and economic crime or corruption. From the research results, it can be seen that both investment has a positive effect on economic growth. On the other hand, crime has a negative impact on regional economic growth.